Analgesic efficacy of three different dosages of intra-articular morphine in arthroscopic knee surgeries: Randomised double-blind trial - Gupta, Babita (Indian J Anaesth, 2015)
BACKGROUND AND AIMS: Arthroscopic knee surgery is a common procedure and may cause enough pain to delay rehabilitation. Intra-articular (IA) morphine is a known modality for post-operative pain relief. However, the optimal dose of IA morphine has not been studied. The current study has been conducted to find out the optimal dosage of IA morphine when administered with 0.25% bupivacaine. METHODS: Sixty adult patients of either sex, aged between 18 and 60 years, undergoing diagnostic/therapeutic knee arthroscopic surgery were included in the study and randomised into three groups. All patients underwent surgery under subarachnoid block. After the surgical closure, 20 ml of 0.25% bupivacaine with 1 mg, 3 mg and 5 mg of morphine as additive was injected intra-articularly in Group A, B and C patients, respectively. Post-operative pain assessment was performed with visual analogue scale score in the 1(st), 2(nd), 6(th), 12(th) and 24(th) post-operative hour. The common complications were also recorded. RESULTS: There was statistically significant analgesia in Group B and C than Group A in the 1(st) and 2(nd) post-operative hour; while at the 24(th) post-operative hour, Group C had statistically significant analgesia than the other two groups. Time to first rescue analgesia was statistically significantly less and consumption of supplemental analgesia was significantly higher in Group A than the other two groups. CONCLUSION: IA dose of 3 mg and 5 mg morphine with 20 ml of 0.25% bupivacaine provided adequate analgesia. However, 3 mg morphine group patients had fewer side effects than 5 mg group patients although the difference was not statistically significant.